South American species Solanum alandiae Card. and S. okadae Hawkes et Hjerting as potential sources of genes for potato late blight resistance - O. A. Muratova (Fadina); M. P. Beketova; M. A. Kuznetsova; E. V. Rogozina; E. E. Khavkin (Труды по прикладной ботанике, генетике и селекции)
For several decades, wild species of Solanum L. section Petota Dumort. have been involved in potato cultivar breeding for robust resistance to pests and diseases. Potato late blight (LB) is caused by oomycete Phytophthora infestans (Mont.) de Bary, and the genes for race-specific resistance to P. infestans (Rpi genes) have been introgressed into cultivated potatoes by remote crosses and trans- or cisgenesis, first from S. demissum Buk. and, more recently, from other wild species, such as S. bulbocastanum Dun., S. stoloniferum Schlechtd. et Bché, and S. venturii Hawkes et Hjerting (according to the nomenclature by Hawkes, 1990). Most wild species already involved in breeding for LB resistance came from North and Central Americas: series Bulbocastana (Rydb.) Hawkes, Demissa Buk. and Longipedicellata Buk., and some Rpi genes of these species have been already characterized in much detail. Rpi genes of South American species, including the series Tuberosa (Rydb.) Hawkes, have not been sufficiently investigated. Among the latter, this study focuses on the Rpi genes of S. alandiae Card. and S. okadae Hawkes et Hjerting. Four accessions of S. alandiae, one accession of S. okadae and 11 clones of interspecific potato hybrids comprising S. alandiae germplasm from the VIR collection were PCR-screened using specific SCAR (Sequence Characterized Amplified Region) markers for eight Rpi genes. SCAR amplicons of five Rpi genes registered in this study were validated by comparing their sequences with those of prototype genes deposited in the NCBI Genbank. Among the structural homologues of Rpi genes found in S. alandiae and S. okadae, of special interest are homologues of CC-NB-LRR resistance genes with broad specificity towards P. infestans races, in particular R2=Rpi-blb3, R8, R9a, Rpi-vnt1 and Rpi-blb2 (94–99, 94–99, 86–89, 92–98 and 91% identity with the prototype genes, respectively). Our data may help to better understand the process of Rpi gene divergence along with the evolution of tuberbearing Solanum species, particularly in the series Tuberosa.